Analisis Sistem Pemerintahan Di Indonesia Pada Demokrasi Di Era SBY Dan Jokowi. - Cindy Nabilla; Irmaline Pakazeni (TheJournalish: Social and Government, 2020)
This article aims to see how the development of the government system in Indonesia through the perspective of democracy in the era of SBY and Joko Widodo. Which is considered to have constraints and problems in several sectors. To find out the results of these objectives, this article uses literature studies with theoretical approvals taken from several sources, both news, journals and books to retrieve the data needed. His findings were that the government system in the democratic era during the leadership of SBY and Joko Widodo was considered to have many problems in the Indonesian political system. The rise of bureaucratic diseases often occurs such as political reciprocation, until the revision of the ITE Law and the weakening of the KPK during the 7th presidential year of the Republic of Indonesia, Joko Widodo, has made public confidence in the government decline. Another finding is the data in the Central Statistics Agency, namely the Indonesian democratic index or IDI is fairly stable and increasing, but in practice the unrest and distrust of the public towards the government system in Indonesia especially democracy in Indonesia is increasingly apparent.